Tennis college - Brett, Bob. ([S.l. : s.n.], 1994)
This instructional video is different from all others, as the tips passed on by by Bob to you are the same as those given to the world's top players that he trains. The tape is based on years of experience and is of invaluable helpto players of all ages and standards
Executive producer, Martin Davey
Keywords: Tennis -- Coaching